Optimal Operation of Solar Battery Chargers via Mixed-Integer Linear Programming - Bianchini, Gianni; Casini, Marco; Laudani, Antonino; Maria Lozito, Gabriele (IEEE control systems letters, 2025)
This letter considers an islanded system consisting of a photovoltaic source connected to a battery storage through power converters, subject to a time varying load. An innovative charging architecture composed of two DC-DC converters and a super-capacitor is considered, and a novel modeling and optimal control framework is proposed with the aim of optimizing battery charge/discharge cycles while satisfying given generation and load profiles. Nonlinearities and nonconvex constraints arising from the electrical models are suitably treated in order to devise an optimal control problem involving linear dynamics that can be solved to the global optimum via mixed-integer linear programming. Numerical simulations based on a real data set show the effectiveness of the proposed approach as well as its computational feasibility.